Breaking the Burnout Cycle Reinventing Employee Well-Being Strategies in Human Resource Management within High-Pressure Organizational Culture - Muhammad Ramdhan; Muhamad Ridwan (PT. Riset Press International, 2025)
This study aims to explore burnout among service-sector employees and examine how Human Resource Management (HRM) strategies can break the burnout cycle through a well-being-oriented approach. The research employed a qualitative method with a phenomenological design to gain a deeper understanding of employees’ lived experiences regarding workplace stress and burnout. Data were collected through in-depth interviews with service-sector employees in Ciamis, Indonesia, who regularly face high work demands and intensive customer interaction. The findings reveal that burnout is primarily caused by excessive workload, time pressure, emotional labor, and continuous interaction with customers, which often leads to emotional exhaustion and decreased work motivation. In addition, inadequate organizational support, limited appreciation, and insufficient opportunities for recovery further intensify burnout conditions among employees. Nevertheless, the study also demonstrates that effective HRM strategies can significantly reduce burnout and improve employee well-being. Supportive leadership, flexible work arrangements, employee recognition, training programs, and open communication were identified as important factors in creating a healthier work environment. Employee well-being emerges as a crucial mechanism that mediates the relationship between job demands and burnout. This study highlights the importance of integrating employee well-being into HRM practices to maintain sustainable employee performance and organizational effectiveness.